Diagnostic Process and Applied Criteria for Crohn’s Disease in Patients Presenting with Perianal Lesions in Japan: A Retrospective Observational Multicenter Cohort Study - Naoto Saigusa; Naoki Hotta; Jun-ichi Saigusa (Inflammatory Intestinal Diseases)
Introduction: In Japan, the confirmed diagnosis of Crohn’s disease (CD) is based on a single, historically established set of clinical criteria. However, for patients who present with a perianal lesion (PL), the diagnostic pattern actually applied is unclear. Methods: We conducted a retrospective observational multicenter study among patients who presented with a PL without synchronous abdominal symptoms and were subsequently diagnosed with confirmed or probable CD according to the Japanese diagnostic criteria from May 1996 to April 2024. In total, 100 patients with confirmed CD and 10 with probable CD were identified and enrolled. Results: Among the 100 patients with confirmed CD, 72% met the criterion for the category “confirmed 1: main finding A (longitudinal ulcer) or B (cobblestone appearance).” In the same cohort, 35% met the criterion for the category “confirmed 2: main finding C (non-caseating epithelioid cell granuloma [NCEG]) with secondary finding a (extensive irregular-to-round ulcers or aphthae in the gastrointestinal tract) or b (characteristic anorectal lesions),” including 24% without the main finding A or B. Finally, 4% met the criterion for the category “confirmed 3: all secondary findings a, b, and c (characteristic gastric and duodenal lesions).” All 10 patients with probable CD were diagnosed based on secondary finding b only or secondary findings a and b. Conclusion: In cases of suspected CD due to initial PLs, histological investigation of NCEG and precise total gastrointestinal inspection should be conducted to confirm the diagnosis.